SAT0025 Antifibrotic effects of imatinib mesylate are not superior to selective inhibition of PDGFR by ARRY-768 in preclinical models of dermal fibrosis. (23rd January 2014) - Tomcik, M.; Reich, N.; Palumbo-Zerr, K.; Zerr, P.; Avouac, J.; Distler, A.; Robinson, J.; Dees, C.; Beyer, C.; Becvar, R.; Senolt, L.; Distler, O.; et al.
Abstract : Background: PDGF (plateled derived growth factor) is one of the key profibrotic cytokines in pathogenesis of systemic sclerosis. ARRY-768 is a highly selective, orally active, small molecule inhibitor of PDGF receptors, which targets PDGFR more potently than imatinib (IC50 of 3 vs. 69 nM, respectively). Objectives: To investigate the efficacy of ARRY-768 in prevention and treatment of pre-established dermal fibrosis induced by bleomycin. Methods: Design for prevention of dermal fibrosis (A) comprised 3 treatment groups injected with bleomycin s.c. for 3 weeks: group I treated with ARRY-768 (kindly provided by Array Biopharma) 50mg/kg p.o. bid, group II and III with imatinib mesylate 50 and 200mg/kg i.p., respectively. Control groups, injected with NaCl (IV) and bleomycin (V) s.c., were treated p.o. with water. Design for the treatment of pre-established dermal fibrosis (B) consisted of 4 treatment groups injected with bleomycin s.c. for 6 weeks. During the last 3 weeks, groups I and II were treated with ARRY-768 30 and 100mg/kg p.o. bid, and groups III and IV with imatinib 50 and 200mg/kg i.p., respectively. Control groups, injected s.c. with NaCl (V) or bleomycin (VI) for 6 weeks or bleomycin for the first 3 and NaCl the last 3 weeks (VII), were treated p.o. with water for the last 3 weeks. A total of 40+56 (A+B) DBA/2 mice were examined weekly for weight, activity and the texture of the fur. Results: Treatment with ARRY-768 50mg/kg (I) in the prevention model (A) reduced dermal thickening by 67±2% (p<0.001), hydroxyproline content by 23±6% (p=0.642) and myofibroblast counts by 47±5% (p<0.001). Control treatment with imatinib (II, III) demonstrated comparable reduction of dermal fibrosis. In bleomycin-induced pre-established dermal fibrosis (B) treatment with ARRY-768 30 (I) and 100mg/kg (II) decreased dermal thickening by 45±2% (p<0.01) and 56±1% (p<0.01), hydroxyproline content by 52±4% (p<0.001) and 55±5% (p<0.001), and myofibroblast counts by 75±6% (p<0.001) and 88±8% (p<0.001), respectively. Control treatment with imatinib (III, IV) showed similar regression of pre-established dermal fibrosis. ARRY-768 demonstrated significant antifibrotic effects in both prevention and treatment of pre-established dermal fibrosis. The treatment with ARRY-768 was well tolerated for 3 weeks at all dosing regimens with no signs of toxicity such as weight loss, decreased activity or changes in the texture of the fur. Conclusions: This is the first study on the anti-fibrotic effects of the selective PDFGR inhibitor ARRY-768. ARRY-768 did not only prevent experimental fibrosis, but also induced regression of pre-established bleomycin-induced fibrosis without toxic side effects. The efficacy of imatinib was not superior to that of ARRY-768, suggesting that the effects of imatinib might be mediated primarily via inhibition of PDGFR, whereas inhibitory effects on c-abl, a downstream mediator of TGFβ, seem to be less relevant. These data highlight the importance of PDGF signaling in fibrotic diseases. Disclosure of Interest: None Declared